2017
DOI: 10.1007/s00421-017-3588-y
|View full text |Cite
|
Sign up to set email alerts
|

High doses of vitamin C plus E reduce strength training-induced improvements in areal bone mineral density in elderly men

Abstract: High doses of antioxidant supplementations may constrain the favorable skeletal benefits of 12 weeks of resistance exercise in healthy elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
0
17
0
2
Order By: Relevance
“…On this matter, research on strength exercise models in humans is scarce and the first published investigations came up with conflicting results. While some reported a positive effect of vitamins C and E on muscle mass and plasma antioxidant status of elderly people [28,29], others showed negative effects on muscle thickness [30] and bone mineral density [31]. Regarding young people, available findings show that supplementation may actually hamper strength gain [32,33] or is ineffective [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…On this matter, research on strength exercise models in humans is scarce and the first published investigations came up with conflicting results. While some reported a positive effect of vitamins C and E on muscle mass and plasma antioxidant status of elderly people [28,29], others showed negative effects on muscle thickness [30] and bone mineral density [31]. Regarding young people, available findings show that supplementation may actually hamper strength gain [32,33] or is ineffective [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent studies demonstrated that 1) aged αTTP knockout mice had reduced cortical bone mass, 2) low dietary Vitamin E intake did not increase bone mass in mature rats, 3) high dietary Vitamin E intake did not reduce cortical bone mass in mature rats, and 4) high Vitamin E intake did not affect cortical bone mass in maturing rats [5,6]. Human studies, likewise, have shown conflicting results regarding the beneficial or detrimental effects of Vitamin E on bone health [7][8][9][10][11][12][13]. Thus, the role of Vitamin E in bone remains unclear and somewhat controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study was carried out for a short time (12 weeks) and in a small group of volunteers, and neither smoking status nor primary VC serum levels were considered. In a similarly projected study [86] with a longer, six-month follow-up, no similar restrictive effect of antioxidant supplementation to benefit from systematic resistance training was seen. No difference was observed between the groups with antioxidant supplementation, systematic physical activity and the connection of both interventions.…”
Section: Interventional Studiesmentioning
confidence: 89%
“…In the other presented clinical trials only laboratory markers of bone metabolism were taken into consideration. The first of them was the study with a design similar to Stunes [86] and Chuin [88] in which the strength training program was one of the tested interventions. The Maïmoun team [68] pilot study recruited nine elderly women and four men to an 8-week experiment with VC (500 mg) and VE (100 mg) supplementation connected with supervised, one-hour training three times a week.…”
Section: Interventional Studiesmentioning
confidence: 99%